Diamond Work's Picture Sdn. Bhd. / Muhammad Shahzil Abu Bakar ... [et al.] - Abu Bakar, Muhammad Shahzil; Tasmidi, Sarina; Othman, Norfaeiza; Kitap, Sophia Sutie; Adam, Muhd Shukry; Rahmat, Noraini; Johari, Mazlin (Faculty of Artistic and Creative Technology, 2002)
Diamond Work s Picture Production Sdn . Bhd is will be one of company has registered as a Production House which involved in Film Industry . The objective of this company is to manage the production for shooting of drama and Telemovie. This company also offers for any individual or company, which tend to make process production. For general, Diamond Work s Picture Production Sdn. Bhd is manufacturer production for drama and Telemovie via steel film in size 16 mm, 35 mm or 75 mm or video form VHS and DV Cam. Other than that, it will be shown in television screen, multimedia Digital or any picture form by using the technology of Telemovie or drama. Diamond Work s Picture Production Sdn Bhd also prepares and produces the expertise and professional manpower for publishing drama and Telemovie. It will be done by our own employee of our production house. However these professional service available as we plan 20 % for our company and 80 % as a freelance to another offer by others company. They will have a great knowledge or skill in particular course as workers in Malaysia industrial film. Our company conducts all activities, which related in Pre-Production via Reece for location, searching props and wardrobes, constructions for art and set direction or casting talent for shooting production of drama or Telemovie. We were also willing 100% for Production Shooting activities. However all of these will and having cooperation with "Kementerian Penerangan Malaysia" and National Film Development Corporation Malaysia (FINAS).